Pengembangan Media Pembelajaran Geografi Berbasis Potensi Lokal untuk Meningkatkan Pemahaman Ruang di Sekolah Kepulauan - Helmi, Dewilna; Hallatu, Yosepus Anthony; Pinoa, Herwic; Rosely, Merti Seska (Universitas Pattimura, 2024)
This community service activity was carried out to enhance the capacity of 30 geography teachers in island schools in Ambon City to develop learning media based on local potential that reflects the region’s geographical characteristics. The activity was motivated by the limited use of contextual media that mirrors students’ real environments. Its goal was to empower teachers to design and utilize learning media that strengthen students’ spatial understanding. The method included participatory mentoring, three-month technical workshops, and classroom implementation. Results showed a 40% improvement in teachers’ ability to design interactive media, a 35% increase in student engagement, and the emergence of school initiatives to build inter-teacher collaboration. The program demonstrated a significant contribution to strengthening locally rooted education in island regions. The approach is recommended for sustainable implementation in other island-based schools across Eastern Indonesia